2016
DOI: 10.1016/j.jmbbm.2015.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Imprecise knowledge based design and development of titanium alloys for prosthetic applications

Abstract: Sultana, N. (2015) Imprecise knowledge based design and development of titanium alloys for prosthetic applications.Journal Abstract Imprecise knowledge on the composition-processing-microstructure-property correlation of titanium alloys combined with experimental data are used for developing rule based models for predicting the strength and elastic modulus of titanium alloys. The developed models are used for designing alloys suitable for orthopaedic and dental applications. Reduced Space Searching Algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…During the last decade, major efforts have been dedicated to studying multicomponent Ti alloys containing non-toxic and non-allergic alloying elements such as Nb, Zr, and Ta due to their appropriate combination of properties: good mechanical properties, high corrosion resistance in body fluids or simulated body fluids, and enhanced biocompatibility [1][2][3][4][5][6]. If one considers the mechanical properties, i.e., the demand for a low modulus of elasticity in implantable biomedical applications [7][8][9], it was demonstrated that the values of elastic modulus are strongly dependent on thermomechanical processing parameters [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, major efforts have been dedicated to studying multicomponent Ti alloys containing non-toxic and non-allergic alloying elements such as Nb, Zr, and Ta due to their appropriate combination of properties: good mechanical properties, high corrosion resistance in body fluids or simulated body fluids, and enhanced biocompatibility [1][2][3][4][5][6]. If one considers the mechanical properties, i.e., the demand for a low modulus of elasticity in implantable biomedical applications [7][8][9], it was demonstrated that the values of elastic modulus are strongly dependent on thermomechanical processing parameters [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Among the available methods for such analysis, the connection weight method 47 is simple and delivers similar results compared to other methods. This method is used in previous studies of materials design, 3536 as well as in this study. This method uses input layer to hidden layer weight and hidden layer to output layer connection weights for the estimation of variable importance.…”
Section: Methodsmentioning
confidence: 99%
“…[33][34][35] GA has been successfully used to design Ti alloys for prosthetic applications. 36 The mechanical and tribological characterization of two designed and developed composites are studied. The structural characterizations are also made to get better understanding of the mechanical and tribological behavior of the material.…”
Section: Introductionmentioning
confidence: 99%
“…The great feature that Ti-6Al-4V (112 GPa), Ti-6Al-7Nb (110 GPa) and other titanium alloys has is a low elastic modulus, close to the elastic modulus of the bone (30 GPa), in comparison with Co-Cr alloys (240 GPa) and AISI 316-L stainless steel (210 GPa) [33]. Amongst the titanium alloys, the Ti-6Al-4V titanium alloy is the most employed in biomedical applications [34]. However, the use of materials that remove vanadium (V-free) from titanium alloys for medical application has been debated since the mid-1980s in the USA [35].…”
Section: Biomaterialsmentioning
confidence: 98%